Efficacy and benefits of catheter ablation of premature ventricular complexes in patients younger and older than sixty-five years of age - Mehmet Akkaya; Henri Roukoz; Selcuk Adabag; Andrew Peter; Jian Ming Li; Venkat Tholakanahalli (KARE Publishing, 2013)
Objectives: Catheter ablation of premature ventricular complexes (PVC) improves clinical status and systolic performance of left ventricle (LV) in certain subset of patients, however whether PVC ablation is equally effective in younger (≤65 years old) and older (>65 years) patients remain unclear. We aimed to assess clinical benefits of catheter ablation of PVCs in elderly patients. Methods: Fifty-one consecutive patients (66+-10 years, 49 male) who underwent catheter ablation for symptomatic PVCs were included into the study. Twenty-seven patients were aged>65 years and 24 patients ≤65 years old. Frequency of PVCs per total heart beats by 24-hour Holter monitoring, LV ejection fraction (LVEF) and end-systolic diameters (LVEDD) were evaluated before and 6+-3 months after ablation. Results: The pre-ablation 24 hour PVC burden and PVC number was significantly higher in patients aged >65 years old compared aged ≤65 years (31+-15.3 vs. 21.9+-12.6; p = 0.04 and 34493+-21226 vs. 23554+-13792; p = 0.026, respectively). At follow up after catheter ablation, the mean PVC burden decreased to 9.1+-10.3% (p<0.001) in patients >65 years while to 3.8+-7.1 (p<0.001) in patients ≤65 years of age. Mean LVEF showed significant increase in both groups after ablation (43.4+-10.4 vs. 51.5+-8.2; p = 0.005 for age>65 years and 40.8+-13.2 vs. 49.5+-11.8; p = 0.003 for age ≤65 years). The improvement in LVEF was accompanied by significant decrease in LV end-diastolic diameter (p = 0.032 for age>65 and p = 0.047 for ≤65 years). Conclusion: Catheter ablation is effective for treatment of frequent PVCs in all age groups.